Is Going Green Good for Profit? Empirical Evidence from Listed Manufacturing Firms in Indonesia - Rokhmawati, Andewi; Gunardi, Ardi (International Journal of Energy Economics and Policy, 2017)
This paper empirically analyses the effects of greenhouse gas (GHG) emissions on the financial performance of listed Indonesian manufacturing firms in 2011. The data of GHG emissions was obtained by personal interviews with relevant officials of sample firms as it is publicly unavailable. This research used four different measures of firm financial performance to understand how stakeholders respond to firms GHG emissions which were measured in CO2e intensity. This study draws on the Instrumental Stakeholder Theory and Competitive Advantage Theory. The results showed that GHG emission has a positive significant effect on all measures of firm financial performance. As the cost of compliance exceeds the cost from non-compliance, and regulatory enforcement is lax, firms have little incentive to comply with GHG regulation. Keywords: GHG emissions; financial performance; Indonesian Manufacturing Firms JEL Classifications: G3; L6; M1; Q5